Quality Control with Six Sigma Method to Minimize Polyester Fabric Product Defects at PT Sukuntex - Laelatul Fitria; Dina Tauhida; Akh Sokhibi (OPSI, 2023)
Quality control needs to be done to face industrial competition. PT. Sukuntex is a textile industry that produces fabrics, one of which is polyester with 58% production from the total fabric production. PT. Sukuntex has a make to order fabric production system, the company carries out quality control by inspecting every fabric produced in the quality control division. In this study, an analysis of polyester fabric quality control using the six sigma method with the DMAI (Define-Measure-Analyze-Improve) steps to determine the DPMO value, the company's sigma level, the causes of defects, and improvements. The results of this study found 3 dominant defects based on the Pareto diagram, namely thin thickness, sparse, and dirty oil. In calculating the DPMO value, the result is 49,825.15 meters with the sigma value obtained is 3.15. The sigma value can increase with quality improvement. Therefore, the causes of defects were analyzed using a fishbone diagram which resulted in human, machine, method, and environmental factors. FMEA-AHP method for improvement priorities, where FMEA analyzes the ranking of the causes of defects, then prioritizes improvement based on weights with AHP. Improvement plan using the 5W+1H method at the improve stage.